Analisis Kemenangan Suryono Pada Pemilihan Kepala Desa Tegalarum Kecamatan Jaken Kabupaten Pati Periode Tahun 2015-2021 (Analisis Figur dan Tim Sukses) - Oktaviano, Okka; Astuti, Puji; ,, Sulistyowati (Journal of Politic and Government Studies, 2017)
The purpose of this study is to analyze the strategies Suryono victory and Team Success In The Village Head Election Tegalarum Jaken District of Pati Regency period 2015-2021. The strategy used Suryono and Success Team to win elections Tegalarum village is preceded by mapping a mass basis, determine the steps for the campaign and also formulate a work program that will be offered to the public. To get more support Suryono and Team Successful use of communication strategies namely by visiting luminaries Tegalarum village society considers people who respected and honored in the Village Tegalarum. Here Suryono and team success always follows the activities organized in the village Tegalarum to introduce themselves while closer to the village community Tegalarum.This research uses qualitative research methods. The subject of research among others Suryono as Tegalarum village chief, Tim Tegalarum Success and village residents are involved in the implementation of the Village Head Election Tegalarum Jaken District of Pati regency. The data collection technique is done through interviews, documentation, literature, and then analyzed to draw conclusions.Based on the results of the study concluded that Suryono Tegalarum elected as village chief in the district of Pati regency period 2015-2021 Jaken gained 917 votes, while Suharto gained 800 votes. In obtaining more votes Suryono and the Campaign Team chose Hamlet Mberan and Hamlet Taunan as a target for support, as in Hamlet Taunan is the home of Suryono and relatives or relatives of Suryono also play an active role in influencing and introducing Suryono to the public, while at the hamlet Mberan many people, especially young kids activities facilitated Suryono relatives such as association youth.Keywords: Village Head Election, Political Strategy, Village Tegalarum